A Congolese-US participatory action research partnership to rebuild the lives of rape survivors and their families in eastern Democratic Republic of Congo - Glass, Nancy; Ramazani, Paul; Tosha, Mafille; Mpanano, Mitima; Cinyabuguma, Matthias (Global public health, 2012)
The Democratic Republic of Congo (DRC) remains an all-too-potent reminder of how war, human rights violations and their related health and economic impacts can devastate a society. The last decade has seen the use of rape as a weapon of war in the DRC, where rebels and soldiers subject women and girls to brutalising attacks, rape, torture and mutilation. Survivors of sexual and gender-based violence (SGBV) are often further traumatised by infections, disease, poverty, stigma and social isolation. Substantial evidence exists showing an association between social determinants (e.g., poverty, stress and trauma, stigma, lack of access to health care) and health; however, limited research has been conducted to elucidate these relationships or to develop and test interventions to change social determinants of health, especially in conflict and post-conflict settings such as the DRC. The purpose of this article is to present a Congolese-US community-academic research partnership to obtain evidence to develop and implement a sustainable intervention to begin to address the social determinants of health, including poverty and traumatic stress for survivors of SGBV and their families in the South Kivu province of eastern DRC.